Undoing subalternity?: Anarchist anthropology and the dialectics of participation and autonomy - Zehmisch, Philipp (Negotiating normativity, 2016)
The chapter aims to critically examine Gayatri Spivak’s efforts to undo subalternity by inserting it into the circuit of hegemony. For Spivak, working for the subaltern does not demand speaking for them, rather it entails facilitating their speech acts. From the perspective of anarchist anthropology, the opening up of political communication towards inclusion of subaltern speech is, on the one hand, an essential goal. It is congruent with the basic democratic principles of consensual decision-making among social groups living outside or at the margins of state influence. On the other hand, the insistence on including subalterns into hegemony entails an inherent paradox: many subalterns, especially indigenous people and groups, who resort to anarchist ways of life, escape from the state and its communicational structures as a survival strategy. My ethnographic example from the Andaman Islands in India addresses this tension. I focus on the subaltern history of the so-called Ranchis, indigenous people from formerly anarchist societies in the Middle Indian hill region. From the perspective of anarchist anthropology, and the ethnographic example of the Ranchis, Spivak’s compelling idea of undoing subalternity appears in a new light: An inclusion of subalterns into the circuits of hegemony would moderately benefit them in terms of getting access to the state and the economy, but at the same time it would also imply a loss of their partial economic, cultural, and social autonomy from the outside world.
Gesehen am 14.12.2021